Leagile manufacturing paradigm in the production of jet pump - an implementation experience. (20th July 2020) - Balakrishnan, K.; Devadasan, S.R.; Thilak, V.M.M.; Soundaram, D. Selvi
One of the types of pumps that find high demand from the customers is jet pumps. Today, pump manufacturing companies are required to produce conventionally designed jet pump as well as improved and innovative forms of the same to meet the demand of several customers. This kind of demand can be fulfilled only when leagile manufacturing paradigm is implemented around the production of jet pumps. In order to have a successful implementation of the same, while pursuing the research reported in this paper, a model named as 'pumping for leagility' (PFL) was designed and applied in the case of producing jet pumps in a typical Indian pump manufacturing company. The PFL model has eight steps comprising of 31 activities. By applying PFL model, the nuances of developing leagile manufacturing paradigm in real-time practice was examined and the extent of implementation in the production of jet pump was studied.